A Distinct Colon‐Derived Breath Metabolome is Associated with Inflammatory Bowel Disease, but not its Complications. Issue 11 (November 2016) - Rieder, Florian; Kurada, Satya; Grove, David; Cikach, Frank; Lopez, Rocio; Patel, Nishaben; Singh, Amandeep; Alkhouri, Naim; Shen, Bo; Brzezinski, Aaron; Baker, Mark; Fiocchi, Claudio; et al.
Abstract : OBJECTIVES: : The accuracy of available noninvasive biomarkers for diagnosis, stratification, and prediction of inflammatory bowel disease (IBD) courses is limited. We analyzed volatile organic compounds (VOCs) in the breath of IBD patients and controls for diagnosis and differentiation of IBD as well as their link with disease location, activity, and phenotype. METHODS: : A prospective study of diagnostic testing was conducted, recruiting Crohn's disease (CD), ulcerative colitis (UC), other inflammatory gastrointestinal diseases (OGDs), and healthy controls (HCs), as well as subjects with ileal pouch anal anastomosis (IPAA). The breath VOC profile was analyzed using selective ion flow tube‐mass spectrometry. RESULTS: : One hundred and twenty‐four subjects ( n =24 CD, n =11 UC, n =6 OGD, n =53 HC, n =30 IPAA) were included. The breath metabolome was significantly different in patients with IBD, CD, or UC compared with OGD and HC (7 out of 22 VOCs), but not between CD and UC. No link between the level of VOCs with complications, disease location, and clinical or radiologic disease activity, as well as lab parameters or type of medication was found. Breath VOCs were markedly different in patients with IPAA compared with any other group (17 out of 22 VOCs) and the presence of pouch inflammation did not alter the VOC levels. CONCLUSIONS: : A specific breath metabolome is associated with IBD and markedly changes in patients with IPAA. Analysis of a broader spectrum of VOCs can potentially aid in the development of breath prints to diagnose or differentiate inflammatory bowel disorders.